MODERN PERSPECTIVES ON CUTANEOUS T-CELL LYMPHOMA: UPDATE ON CLASSIFICATION, AND EVOLVING THERAPEUTIC STRATEGIES - Ariel Ekaputra; Putu Dyah Ayu Saraswati; Edward Edwin; Dana Parama Julius (SEHAT : Jurnal Kesehatan Terpadu, 2025)
Cutaneous T-cell lymphoma (CTCL) is a heterogeneous group of primary cutaneous non-Hodgkin lymphomas, predominantly represented by mycosis fungoides (MF) and Sézary syndrome (SS), with updated WHO-EORTC and WHO 5th edition classifications incorporating molecular and immunophenotypic criteria that better distinguish indolent subtypes—such as MF, SS, primary cutaneous CD30+ lymphoproliferative disorders, and primary cutaneous acral CD8+ T-cell lymphoma from aggressive variants including primary cutaneous γδ T-cell lymphoma and extranodal NK/T-cell lymphoma. Diagnosis requires integrated clinicopathologic assessment supported by immunophenotyping and clonality studies, while the ISCL/EORTC TNMB staging remains fundamental for prognostication and guides stage-based management, ranging from skin-directed therapy in early-stage to systemic, immunomodulatory, biologic, and targeted approaches in advanced disease. Advances in molecular profiling and biomarker development are expected to further refine risk stratification and support personalized therapy.